2022
DOI: 10.3348/kjr.2021.0771
|View full text |Cite
|
Sign up to set email alerts
|

MRI Findings in Trigeminal Neuralgia without Neurovascular Compression: Implications of Petrous Ridge and Trigeminal Nerve Angles

Abstract: Objective To determine the anatomical characteristics of the petrous ridge and trigeminal nerve in trigeminal neuralgia (TN) without neurovascular compression (NVC). Materials and Methods From May 2017 to March 2021, 66 patients (49 female and 17 male; mean age ± standard deviation [SD], 56.8 ± 13.3 years) with TN without NVC and 57 controls (46 female and 11 male; 52.0 ± 15.6 years) were enrolled. The angle of the petrous ridge (APR) and angle of the trigeminal nerve (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
0
1
Order By: Relevance
“…Ha et al [33] proposed that a smaller TPA was more likely to result in adhesions between the trigeminal root and the arachnoid around the cerebral bridge, increasing the likelihood of contact with blood vessels. However, contrary to our study previous research [34,35] suggested that APR and ATN could serve as predictors of TN In our study, they did not emerge as effective predictors, possibly due to age-related osteophytic changes causing bone spurs to become sharper, and resulting decreased APR and ATN. [36] Age might play a role in the onset of TN, emphasizing the need for a stratified analysis of patients within the same age group or with similar degree of bone hyperplasia, but the lack of appropriate criteria for patients grouping limits this investigation.…”
Section: Discussioncontrasting
confidence: 99%
“…Ha et al [33] proposed that a smaller TPA was more likely to result in adhesions between the trigeminal root and the arachnoid around the cerebral bridge, increasing the likelihood of contact with blood vessels. However, contrary to our study previous research [34,35] suggested that APR and ATN could serve as predictors of TN In our study, they did not emerge as effective predictors, possibly due to age-related osteophytic changes causing bone spurs to become sharper, and resulting decreased APR and ATN. [36] Age might play a role in the onset of TN, emphasizing the need for a stratified analysis of patients within the same age group or with similar degree of bone hyperplasia, but the lack of appropriate criteria for patients grouping limits this investigation.…”
Section: Discussioncontrasting
confidence: 99%